Delayed sampling of intraoperative parathormone may be unnecessary during parathyroidectomy in kidney-transplanted and dialysis patients - Silveira,Andre Albuquerque (2021)
Abstract Introduction: Some authors advise in favor of delayed sampling of intraoperative parathormone testing (ioPTH) during parathyroidectomy in dialysis and kidney-transplanted patients. The aim of the present study was to evaluate the intensity and the role of delayed sampling in the interpretation of ioPTH during parathyroidectomy in dialysis patients (2HPT) and successful kidney-transplanted patients (3HPT) compared to those in single parathyroid adenoma patients (1HPT). Methods: This was a retrospective study of ioPTH profiles in patients with 1HPT, 2HPT, and 3HPT operated on in a single institution. Samples were taken at baseline ioPTH (sampling at the beginning of the operation), ioPTH-10 min (10 minutes after excision of the parathyroid glands), and ioPTH-15 min (15 minutes after excision of the parathyroid glands). The values were compared to baseline. Results: Median percentage values of ioPTH compared to baseline (100%) were as follows: 1HPT, ioPTH-10 min = 20% and ioPTH-15 min = 16%; 2HPT, ioPTH-10 min = 14% and ioPTH-15 min = 12%; 3HPT, ioPTH-10 min = 18% and ioPTH-15 min = 15%. Discussion: The reduction was equally effective at 10 minutes in all groups. In successful cases, ioPTH decreases satisfactorily 10 minutes after parathyroid glands excision in dialysis and transplanted patients, despite significant differences in kidney function. The postponed sampling of ioPTH appears to be unnecessary.